The Best Software Writing I: Selected and Introduced by Joel Spolsky - Spolsky, Joel (Apress, 2013)
New York City is a blast. Just the other day, as I was walking the four blocks from my office to the subway entrance, interesting things kept happening. Not really interesting things, just modestly interesting things. So, for example, some guy was running down the sidewalk frantically, looking very much like a character in an R. Crumb comic, flapping his arms broadly and making chicken sounds. Running isn’t the right word. He was kind of pratfalling repeatedly and then catching himself right before he hit the ground. Then a taxi turning the corner nearly knocked over an old man who was crossing the street a little bit too slowly for the taxi driver’s taste. A couple of chubby, red-faced out-of-towners asked me if there was a bar anywhere nearby. (There was. We were in front of it.) Someone was handing out little advertising cards at the entrance to the subway. Of course, the inside of the subway station was completely littered with the cards because everybody who took one immediately hurled it on the ground as violently as you can hurl a four-by-six postcard. I almost slipped on one on the steps down.